How the Health Advocate Role is reflected in health professions education literature: a scoping review protocol (Canadian Medical Education Journal, 2026)
The Health Advocate Role remains challenging to teach, assess, and study. Mapping the health professions education (HPE) literature—while considering the influence of context—can offer a more nuanced understanding of how the role is conceptualized and enacted across the HPE landscape. This scoping review aims to support the contextualized implementation of the Health Advocate Role.